Design of IOT-Based Body Temperature Monitoring Prototype at Syekh-Yusuf Islamic University Tangerang Using Black Box Testing Method - Wulan Kurniawati; Asep Abdul Sofyan; Fauzi; Haryanto; Djamaludin (IJESS International Journal of Education and Social Science, 2023)
The spread of the Coronavirus Disease (Covid-19) virus since 2019 has caused a pandemic in this world. Generally, the existing body temperature checkers only function to check the temperature, and allow someone to escape from the process. By utilizing the Internet of Things, it is possible to make a body temperature checking device that can measure measurement data into a database, and display it on a smartphone through an application and this tool is named the Design and Build of a Prototype of Internet of Things-Based Body Temperature Monitoring. The tool uses an infrared temperature sensor which functions to measure contactless body temperature and before using the sensor must be accessed using a Radio Frequency Identification (RFID) card so that data that has checked body temperature can be stored. The data is stored in a database and can also be accessed in the form of a website using the black box testing method. This method is used to find out if the software is working properly. With this tool the screening process becomes more leverage, because the tool can record the temperature of the user of the tool and can store it in the database.